Volatile Molecule Profiles and Anti-Listeria monocytogenes Activity of Nisin Producers Lactococcus lactis Strains in Vegetable Drinks - Siroli, Lorenzo; Camprini, Lucia; Pisano, Maria Barbara; Patrignani, Francesca; Lanciotti, Rosalba (Frontiers in Microbiology, 2019)
This work aimed to evaluate the potential of 15 nisin producing Lactococcus lactis strains, isolated from dairy products, for the fermentation of soymilk and carrot juice. In particular, the acidification and the production of nisin in the food matrices were recorded. Moreover, three strains (LBG2, FBG1P and 3LC39), that showed the most promising results were further scrutinized for their anti-Listeria monocytogenes activity and volatile molecules profile during fermentation of soymilk and carrot juice. Lactococcus lactis strains LBG2, FBG1P and 3LC39 resulted the most interesting ones, showing rapid growth and acidification on both food matrices. The higher amounts of nisin were detected in soymilk samples fermented by the strain LBG2 after 24 and 48h (26.4 mg/L). Furthermore, the rapid acidification combined with the production of nisin resulted in a strong anti-Listeria activity, reducing the pathogen loads below the detection limit, in carrot juice samples fermented by the strains LBG2 and FBG1P and in soymilk by the strain LBG2. The fermentation increased the presence of volatile molecules such as aldehydes and ketones with a positive impact on the organoleptic profile of both the fermented products. These results highlighted the interesting potential of three nisin producing Lactococcus lactis strains for the production of fermented carrot juice and soymilk. In fact, the fermentation by lactic acid bacteria, combined or not with other mild technologies, represents a good strategy for the microbiological stabilization of these products. Furthermore, the increase of molecules with a positive sensory impact, such as aldehydes and ketones, in the fermented products suggests a possible improvement of their organoleptic characteristics.